ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA MANUFAKTUR PADA PROSES PEMBUATAN SUKU CADANG MOBIL ARM VISOR SHAFT - Budianti, Endah Asti; Rizal, Reda (Bina Teknika, 2015)
PT. XYZ is a manufacture company of vehicle spare parts. One of the product is Arm Visor Shaft D01N. The process of making Arm Visor Shaft D01N can be exposed to be potential risk for workers. The source of potential risk is from the material, equipment, machine, environment and the other hazards. Therefore the risk management of occupational health and safety is very important to be implemented in the company. Hazard identification method using the Job Safety Analysis (JSA), while for risk analysis is undertaken by semi-quantitative method that uses risk assessment criteria (consequence, probability and exposure). Based on the research that the level of risk in the process of making Arm Visor Shaft are risk with very high level has 8, substantial level has 23, priority 2 level has 2 and acceptable level has 3.